PENGARUH HAMBATAN SAMPING, U-TURN DAN JALINAN TERHADAP VOLUME LALU LINTAS RUAS JALAN MENUJU ARAH NUSA DUA PADA SIMPANG DEWA RUCI - Gede Sumarda; IB Gede Indramanik; I Nyoman Budiasa (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Traffic congestion on the road towards Nusa Dua at the DewaRuci intersection is caused by several main factors, including Side Obstacles, U-turn and Braided. In analyzing the performance of roads in this study using the Manual of Indonesian Road Capacity 1997, while to obtain a model of the relationship between traffic volume and the factors that influence it using regression analysis. The regression analysis was carried out using the help of a computer program, namely the Static Package for the Social Sciences version 26. The results showed that the highest traffic volume occurred during the peak hours of the day at 4575.85 pcu/hour, capacity 5076 pcu/hour so that the value of the degree of saturation is 0.90 and the level of service at level E. The results of the analysis obtained are in the form of multiple linear regression equations, with the model of the relationship between traffic volume and the factors that influence it shown by the equation Y=886.203+0.190X1+2.360X2+0.570X3.